Vibrations and waves - Bogusz, W. (Wadysaw), 1916-1979; Kaliski, Sylwester; Solarz, Lech, 1937- (Studies in applied mechanics, 1992)
This book gives a comprehensive overview of wave phenomena in different media with interacting mechanical, electromagnetic and other fields. Equations describing wave propagation in linear and non-linear elastic media are followed by equations of rheological models, models with internal rotational degrees of freedom and non-local interactions. Equations for coupled fields: thermal, elastic, electromagnetic, piezoelectric, and magneto-spin with adequate boundary conditions are also included. Together with its companion volume Vibrations and Waves. Part A: Vibrations this work provides a wealth of information about dynamical phenomena in different media and fields, which will be of considerable interest to both scientists and graduate students.